Enhancing Personnel Performance Through Competence and Leadership: The Mediating Role of HR Development as a Catalyst for Economic Advancement in the North Sumatra Regional Police - Liana, Tri Melda Mei; Soekatendel, Edy Wijaya; Aryanti, Meilisa (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to analyze the influence of competence and leadership on personnel performance, with HR development as a mediating variable, within the General Planning and Budget Function of the North Sumatra Regional Police and its affiliates. The research adopts a quantitative approach, involving a population of 496 personnel, from which 84 respondents were selected using the Slovin formula. Data collection was conducted through surveys, and analysis was performed using SmartPLS software. The findings reveal that competence does not have a significant direct effect on personnel performance, although it significantly contributes to HR development. Leadership, on the other hand, has a significant direct effect on personnel performance but does not significantly influence HR development. HR development itself plays a critical role in enhancing personnel performance. Moreover, the mediating analysis shows that HR development significantly mediates the relationship between competence and personnel performance. However, the mediation effect of HR development on the relationship between leadership and personnel performance is not significant. These results underscore the importance of HR development as a strategic factor in improving personnel performance. The findings also highlight the need for the North Sumatra Regional Police to prioritize enhancing competence and leadership quality as part of its HR development initiatives. This study contributes to the understanding of organizational performance within law enforcement agencies and serves as a valuable reference for decision-making and policy formulation aimed at optimizing personnel performance and supporting broader organizational objectives.